Kebijakan Penanggulangan Prostitusi dalam Perspektif Feminisme di Indonesia - Ditha Bianda (CV Rewang Rencang, 2025)
Prostitution is a controversial phenomenon within the fabric of society. This study reveals a legal ambiguity in Indonesia’s national policy, which neither clearly prohibits nor permits prostitution. At the same time, several regional governments have enacted repressive measures against those involved in sex work. This ambiguous approach has drawn attention from feminist groups, who are divided into two major perspectives: those who oppose prostitution and those who support it. Feminism, as an analytical framework, offers alternative policy approaches to address prostitution—ranging from full criminalization, neo-abolitionism, legalization, to decriminalization. The goal is to develop a policy that is fair, inclusive, and responsive to the social realities faced by sex workers.